2018
DOI: 10.1017/langcog.2017.27
|View full text |Cite
|
Sign up to set email alerts
|

L1 + L2 to the power of culture: acculturation and language use for cognitive domains in bilinguals

Abstract: This paper investigates the extent of second language (L2) use in four cognitive domains including mental calculation, planning (action plans), note-taking, and shopping lists. Participants include 149 highly educated L2-competent sequential Polish–English bilinguals who relocated to the UK1 in early adulthood, and underwent processes of acculturation. The independent variables in this study include acculturation level, social network profile, predicted future domicile, and length of residence. The study emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Participants reported using English most frequently in thinking of events that had happened in L2, followed by keeping a diary, praying, and thinking of events that happened in L1. In a follow-up study, Hammer (2018) fond that participants reported using English most frequently in note-taking, followed by shopping lists, action plans, and mental calculation. In particular, the difference in frequency of use between mental calculation and the three other domains was found to be statistically significant.…”
Section: Language Preference and Domains In Inner Speechmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants reported using English most frequently in thinking of events that had happened in L2, followed by keeping a diary, praying, and thinking of events that happened in L1. In a follow-up study, Hammer (2018) fond that participants reported using English most frequently in note-taking, followed by shopping lists, action plans, and mental calculation. In particular, the difference in frequency of use between mental calculation and the three other domains was found to be statistically significant.…”
Section: Language Preference and Domains In Inner Speechmentioning
confidence: 99%
“…In both studies, acculturation level and social network profiles were linked to the preference for English LX in inner speech across the various domains. Both Dewaele (2015) and Hammer (2017aHammer ( , 2018 used cross-sectional designs that yielded data suggesting that the development of LX inner speech across domains is highly dynamic and the amount of inter-individual variation is considerable.…”
Section: Language Preference and Domains In Inner Speechmentioning
confidence: 99%
See 1 more Smart Citation
“…Although heritage bilinguals are sometimes compared to lowproficiency "imbalanced" bilinguals, they are distinct in a number of relevant features (Kupisch & Rothman,2018;Rothman, 2009), including the age of acquisition of the "nondominant" language and language profiles in adulthood. Bilinguals often have a preferred language depending on domain and/or communication objective (Dewaele, 2006;Grosjean, 2015;Hammer, 2018;Hoffman, 1971). Many U.S. heritage bilinguals are educated nearly exclusively in English, resulting in more academic vocabulary and/or literacy skill in English.…”
Section: Heritage Bilinguals and Real-world Contextsmentioning
confidence: 99%
“…Extensive L2 use and high-scale immersion in the host culture can lead to a shift in patterns of language use, and ultimately to restructuring at cognitive (Grosjean 2002;Pavlenko 2014), and emotional (Hoffman 1989) levels. The latter links with processes of acculturation and language shift at an individual level (Hammer 2015;Hoffman 1989). De Leersnyder, Mesquita and Kim (2011) argue that shifts in emotional patterns, in other words, emotional acculturation, may occur as a result of changes of sociocultural contexts.…”
mentioning
confidence: 99%